Get expert advice and community support on IDNLearn.com. Whether it's a simple query or a complex problem, our experts have the answers you need.
Sagot :
Answer:
A, C, E
Step-by-step explanation:
By analyzing the graph, we can see that the roots are [tex]-2[/tex] and [tex]-4[/tex].
We now want to find all equations of the form [tex](x-(-2))(x-(-4))=(x+2)(x+4)=0[/tex].
This immediately gives C as 1 answer.
We can expand our equation to find other possible solutions!
By the FOIL method: [tex](x+2)(x+4)=(x)(x)+(2)(x)+(4)(x)+(2)(4)=x^2+6x+8=0[/tex]
We can then divide both sides of the equation to find that [tex]-x^2-6x-8=0[/tex], so A is another answer.
We can complete the square on [tex]x^2+6x+8[/tex] to find the last possible solution.
[tex]x^2+6x+8=x^2+6x+9-9+8=x^2+6x+9-1=(x+3)^2-1=0[/tex].
We can then multiply both sides of the equation by [tex]4[/tex] to find that [tex]4(x+3)^2-4=0[/tex], so E is the last answer.
The proof that the other answers don't work is left as an exercise.
So, the answers are A, C, and E, and we're done!
Answer:
its going to be letter b because 2 and 4 well the x intercepts those
Step-by-step explanation:
Thank you for participating in our discussion. We value every contribution. Keep sharing knowledge and helping others find the answers they need. Let's create a dynamic and informative learning environment together. For trustworthy and accurate answers, visit IDNLearn.com. Thanks for stopping by, and see you next time for more solutions.